2010
DOI: 10.1086/654929
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inflammation Is Induced by Blood Degradation Products with Microbial Toll‐Like Receptor Agonists and Is Blocked by Hemopexin

Abstract: Detection of microbial components by immune cells via Toll-like receptors (TLRs) with subsequent induction of inflammation is essential for host defense. However, an overactive immune response can cause tissue damage and sepsis. The endogenous molecule hemoglobin and its derivative heme are often released into tissue compartments where there is infection in the presence of degrading blood. We found that hemoglobin synergizes with multiple TLR agonists to induce high levels of tumor necrosis factor and interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 48 publications
3
88
0
2
Order By: Relevance
“…78 Within these complex disease processes, hemin could act as an activator of innate immunity via pattern recognition receptor activation (eg, TLR-4), via synergistic effects with microbial products or endogenous pro-inflammatory ligands (eg, HMGB1), or via peroxidative tissue damage. 24,79,80 Studies in mice suggested that the net effect of free hemin in polymicrobial sepsis could be detrimental and that neutralization of hemin by Hpx administration ameliorates this effect. 78 The protective action of Hpx in sepsis may involve the control of excessive hemin peroxidative activity, inhibition of innate immunity receptor interactions, and redirection of free hemin away from susceptible tissues toward clearance in the liver.…”
Section: The Role Of Hb Heme and Their Scavenger Proteins In Specifmentioning
confidence: 99%
“…78 Within these complex disease processes, hemin could act as an activator of innate immunity via pattern recognition receptor activation (eg, TLR-4), via synergistic effects with microbial products or endogenous pro-inflammatory ligands (eg, HMGB1), or via peroxidative tissue damage. 24,79,80 Studies in mice suggested that the net effect of free hemin in polymicrobial sepsis could be detrimental and that neutralization of hemin by Hpx administration ameliorates this effect. 78 The protective action of Hpx in sepsis may involve the control of excessive hemin peroxidative activity, inhibition of innate immunity receptor interactions, and redirection of free hemin away from susceptible tissues toward clearance in the liver.…”
Section: The Role Of Hb Heme and Their Scavenger Proteins In Specifmentioning
confidence: 99%
“…Macrophage Culture and Cytokine Assays Bone marrow-derived macrophages (BMDMs) were prepared from mice as we described previously (12). BMDMs were washed three times in serum-free medium, followed by incubation overnight with LPS with or without hemin or hemoglobin in the presence or absence of Fc-hHx or Fc or hHx-B in the culture as noted.…”
Section: Purified and Recombinant Hemopexin: Protease Activity And Efmentioning
confidence: 99%
“…Hemin chloride was purchased from Frontier Scientific Inc. Hemin solutions were made immediately before use in the dark as described previously (12). Chemoattractants N-formyl-l-methionyll-leucyl-l-phenylalanine (fMLF) and leukotriene B4 (LTB4) were purchased from Sigma-Aldrich and Cayman Chemical, respectively.…”
Section: Materials and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood transfusion leading to stimulation of the heme breakdown pathway and accumulation of heme catabolites was associated with anti-inflammatory and immunosuppressive effects in multiple animal models, and such effects could contribute to the immunecompromised state of severely ill and massively transfused patients (Yazdanbakhsh et al 2011). On the other hand, proinflammatory effects may be triggered by free heme through the stimulation of toll-like receptor 4 (TLR-4), by reaction intermediates emanating from Hb/ heme peroxidative reactions with phospholipids, or by Hb/heme breakdown products (D'Agnillo and Alayash 2001; Jeney et al 2002;Jia et al 2007;Lin et al 2010;Yazdanbakhsh et al 2011). In a mouse blood transfusion model, older stored RBCs induced an acute phase cytokine release response that accompanied the clearance of transfused RBCs in the spleen (Hod et al 2010).…”
Section: Transfusion Of Stored Bloodmentioning
confidence: 99%